The Pattern of Cleanliness:A Study of Environmental Psychology of Urban Waste Management - Wibowo, Istiqomah (Makara Human Behavior Studies in Asia, 2009)
The purpose of this study was to obtain a theoretical model on cleanliness behavior of the urban society. This model was built based on the pattern of cleanliness behavior which was studied by observing the psychological factors within the individual and the socio-physical factors related to the participants. The indicator used to measure the cleanliness of the environment was the quantity of garbage scattered around the observed location. By living in the society, the researchers could observe and investigate the occurance of cleanliness behavior in the urban region. Direct observation was conducted in 4 (four) clean and 4 (four) dirty group of locations. Qualitative methods were used to process the information from those groups, in order to get significant information regarding the differences and similarities from those locations. The result showed that society’s day-to-day collective action toward garbage created a pattern of cleanliness behavior that is relatively permanent. A series of collective actions which were not in accordance with the communal motive formed cleanliness behavior pattern “X” and created a condition of dirty environment. Meanwhile, the other series of collective actions which were in accordance with the communal motives formed cleanliness behavior pattern “Y”. The collective efforts of the society in a p